Electrochemical Sensing and Assessment of Parabens in Hydro-Alcoholic Solutions and Water Using a Boron-Doped Diamond Electrode - Radovan, Ciprian (Molecular Diversity Preservation International (MDPI), 2008)
In this paper, the electrochemical behaviour of several parabens preservatives, i.e. esters of p-hydroxybenzoic acid, methyl-, ethyl- and propyl-4-hydroxybenzoates as methyl-, ethyl- and propyl-parabens (MB, EB, and PB), has been investigated at a commercial boron-doped diamond electrode (BDDE), especially in the anodic potential range, in both hydro-alcoholic and aqueous media. The cyclic voltammetric and chronoamperometric measurements yielded calibration plots with very good linearity (R(2) between 0.990 and 0.998) and high sensitivity, useful for detection and analytical applications. The determination of the characteristics of individual compounds, of an “overall paraben index”, the assessment of the stability and the saturation solubility in water, and the amperometric sensing and determination in double distilled, tap and river water matrix of the relatively slightly soluble investigated parabens have been carried out using electrochemical alternative. Estimated water solubility was correlated with the octanol-water partition coefficient. Several ideas regarding stability and persistence of the presumptive eco-toxic investigated preservatives in the environment or water systems have been adjacently discussed.